Recent Advances in TiO2-Based Heterojunctions for Photocatalytic CO2 Reduction With Water Oxidation: A Review - Li, Kai; Teng, Chao; Wang, Shuang; Min, Qianhao (Frontiers in Chemistry, 2021)
Photocatalytic conversion of CO2 into solar fuels has gained increasing attention due to its great potential for alleviating the energy and environmental crisis at the same time. The low-cost TiO2 with suitable band structure and high resistibility to light corrosion has proven to be very promising for photoreduction of CO2 using water as the source of electrons and protons. However, the narrow spectral response range (ultraviolet region only) as well as the rapid recombination of photo-induced electron-hole pairs within pristine TiO2 results in the low utilization of solar energy and limited photocatalytic efficiency. Besides, its low selectivity towards photoreduction products of CO2 should also be improved. Combination of TiO2 with other photoelectric active materials, such as metal oxide/sulfide semiconductors, metal nanoparticles and carbon-based nanostructures, for the construction of well-defined heterostructures can enhance the quantum efficiency significantly by promoting visible light adsorption, facilitating charge transfer and suppressing the recombination of charge carriers, resulting in the enhanced photocatalytic performance of the composite photocatalytic system. In addition, the adsorption and activation of CO2 on these heterojunctions are also promoted, therefore enhancing the turnover frequency (TOF) of CO2 molecules, so as to the improved selectivity of photoreduction products. This review focus on the recent advances of photocatalytic CO2 reduction via TiO2-based heterojunctions with water oxidation. The rational design, fabrication, photocatalytic performance and CO2 photoreduction mechanisms of typical TiO2-based heterojunctions, including semiconductor-semiconductor (S-S), semiconductor-metal (S-M), semiconductor-carbon group (S-C) and multicomponent heterojunction are reviewed and discussed. Moreover, the TiO2-based phase heterojunction and facet heterojunction are also summarized and analyzed. In the end, the current challenges and future prospects of the TiO2-based heterostructures for photoreduction of CO2 with high efficiency, even for practical application are discussed.